Finite element based fatigue crack growth of cracked plates under axial loading - Mohamad Abiddullah, Mohd Lasim (2010)
This project deals with the finite element based crack growth of the plate under axial loading. The structural model of cracked plate is developed using solidworks software. The finite element modelling and analysis of crack plate were performed utilizing the MSC.PATRAN and MSC.NASTRAN software respectively. The linear elastics method is used for crack growth analysis, it can be seen that Tetrahedral 10 chosen to be use for the overall analysis because it the TET10 are able to capture the higher stresses compared to TET4 for the same mesh global length and maximum principal stress with meshing sizes 0.2 mm. For the crack growth analysis, surface crack is the suitable orientation compared to other orientation with given the longer life (cycles).